Biocompatibility of poly(ethylene glycol) and poly(acrylic acid) interpenetrating network hydrogel by intrastromal implantation in rabbit cornea. Issue 10 (27th March 2015) - Luo Zheng, Luo; Vanchinathan, Vijay; Dalal, Roopa; Noolandi, Jaan; Waters, Dale J.; Hartmann, Laura; Cochran, Jennifer R.; Frank, Curtis W.; Yu, Charles Q.; Ta, Christopher N.
Abstract We evaluated the biocompatibility of a poly(ethylene glycol) and poly(acrylic acid) (PEG/PAA) interpenetrating network hydrogel designed for artificial cornea in a rabbit model. PEG/PAA hydrogel measuring 6 mm in diameter was implanted in the corneal stroma of twelve rabbits. Stromal flaps were created with a microkeratome. Randomly, six rabbits were assigned to bear the implant for 2 months, two rabbits for 6 months, two rabbits for 9 months, one rabbit for 12 months, and one rabbit for 16 months. Rabbits were evaluated monthly. After the assigned period, eyes were enucleated, and corneas were processed for histology and immunohistochemistry. There were clear corneas in three of six rabbits that had implantation of hydrogel for 2 months. In the six rabbits with implant for 6 months or longer, the corneas remained clear in four. There was a high rate of epithelial defect and corneal thinning in these six rabbits. One planned 9‐month rabbit developed extrusion of implant at 4 months. The cornea remained clear in the 16‐month rabbit but histology revealed epithelial in‐growth. Intrastromal implantation of PEG/PAA resulted in a high rate of long‐term complications. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3157–3165, 2015.